PENGARUH STRATEGI INOVASI TERHADAP KEUNGGULAN BERSAING PADA INDUSTRI PARIWISATA DI KABUPATEN LANGKAT - Merry Moy Mita; Richard Djiko; Nerys Lourensius L. T (Journal of Global Business and Management Review, 2022)
The large variety of tourist objects in Langkat Regency, of course, provides many choices for tourists to do recreation. Therefore the need for an innovation strategy in creating competitive advantages in the tourism industry. This study aims to determine the effect of innovation strategy on competitive advantage in the tourism industry of Kab. Langkat. The sample in this study were students, local workers and the community who traveled in Kab. Langkat, with a sample of 122 respondents with the sampling method used is purposive sampling. The dependent variable in this study is competitive advantage and the independent variables in this study are leadership orientation, type of innovation, source of innovation and level of investment. The research method used is a quantitative method with primary data obtained from questionnaire data measured by a Likert scale. The data analysis technique used in this research is multiple linear regression analysis. Research data was collected using a questionnaire which was then processed using the SPSS 21.0 program. The results obtained from this study are that the innovation strategy has an effect on competitive advantage in the tourism industry in Langkat Regency.